The Influence of Affiliate Marketing, Live Streaming, Flash Sales, and Online Customer Reviews on Purchasing Decisions on TikTok Shop (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to determine the effect of affiliate marketing, live streaming, flash sales, and online customer reviews on purchasing decisions among users of the Tiktok Shp application. The population in this study were students of the Faculty of Creative Design and Digital Business, ITSNU Pekalongan. The sample used in this study used the purposive sampling method. The type of data used was primary data by means of a questionnaire. The analysis technique used was multiple linear regression analysis using SPSS version 30. The results of the study partially showed that: (1) Affiliate Marketing had a positive effect on purchasing decisions with a significance of 0.001
Keywords: Affiliate Marketing; Live Streaming; Flash Sale; Online Customer Review